Recent progress in drug delivery - Chong Li; Jiancheng Wang; Yiguang Wang; Huile Gao; Gang Wei; Yongzhuo Huang; Haijun Yu; Yong Gan; Yongjun Wang; Lin Mei; Huabing Chen; Haiyan Hu; et al. (Elsevier, 2019)
Drug delivery systems (DDS) are defined as methods by which drugs are delivered to desired tissues, organs, cells and subcellular organs for drug release and absorption through a variety of drug carriers. Its usual purpose to improve the pharmacological activities of therapeutic drugs and to overcome problems such as limited solubility, drug aggregation, low bioavailability, poor biodistribution, lack of selectivity, or to reduce the side effects of therapeutic drugs. During 2015-2018, significant progress in the research on drug delivery systems has been achieved along with advances in related fields, such as pharmaceutical sciences, material sciences and biomedical sciences. This review provides a concise overview of current progress in this research area through its focus on the delivery strategies, construction techniques and specific examples. It is a valuable reference for pharmaceutical scientists who want to learn more about the design of drug delivery systems. KEY WORDS: Pharmaceutics, Drug delivery system, Basic research, Application, Delivery strategy